1999
DOI: 10.1164/ajrccm.160.6.9812055
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Critically Ill Cancer Patients in a University Hospital Setting

Abstract: Critically ill cancer patients constitute a large percentage of admissions to tertiary care medical intensive care units (ICUs). We sought to describe outcomes of such patients, and to evaluate how conditions commonly seen in these patients impact mortality. A total of 348 consecutive medical ICU cancer patients were evaluated. Subgroup comparisons included the three most common cancer types (leukemia, lymphoma, lung cancer), as well as three different treatments/conditions (bone marrow transplant [BMT] versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
108
2
19

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(148 citation statements)
references
References 33 publications
19
108
2
19
Order By: Relevance
“…According to the literature, during their hospitalization, survival of cancer patients admitted to the intensive care unit is mainly influenced by the physiological disturbances caused by the complications leading to ICU admission [10,14,17]. We confirmed these observations in the present study, highlighting in particular the SOFA score, but also easily measurable variables like fever and GOT.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…According to the literature, during their hospitalization, survival of cancer patients admitted to the intensive care unit is mainly influenced by the physiological disturbances caused by the complications leading to ICU admission [10,14,17]. We confirmed these observations in the present study, highlighting in particular the SOFA score, but also easily measurable variables like fever and GOT.…”
Section: Discussionsupporting
confidence: 89%
“…The same low percentage of ICU admissions (3 %) of patients with colorectal cancer was found in a study dealing with both solid and hematological tumors [14]. The frequency of digestive cancers among solid tumors admitted in ICU is between 7 and 17 % in other series [10,15].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Although NPPV also appears to be useful in the initial stage of acute respiratory failure, treatment with NPPV alone was unsuccessful in the majority of cases, and the failure of the initial NPPV treatment may be associated with a prognosis (14). The above results appear to indicate a need for stringent monitoring to ensure that there is no delay in the progression from NPPV to IMV, and that an ICU is a preferable treatment environment to a sterile ward (17).…”
Section: Discussionmentioning
confidence: 99%
“…The high mortality of more than 80% in patients requiring mechanical ventilation (Table 1) [8][9][10][11][12][13][14][15] , increasing to more than 90% to 95% in patients developing multiple organ failure or who require renal replacement therapy during ICU stay 12,[16][17][18] , particularly in the transplant setting [19][20][21] , together with the severe emotional burden endured by these patients and their relatives, and the considerable costs of advanced and prolonged life-supporting therapy 13 resulted in a general reluctance to admit such patients to the ICU 2,6,7 . However, over the past few years, several centres throughout the world have been reporting on increasingly improving survival in critically ill patients with hematological malignancies and solid tumors [22][23][24][25][26][27][28][29][30][31] , approaching survival rates reported in general ICU patients 32 . In a case-historical control study 22 , Azoulay et al reported a four-fold lower risk of death in cancer patients who required mechanical ventilation between 1996 and 1998 as compared with 1990-1995.…”
Section: Outcome In Critically Ill Cancer Patients: Evolution Over Thmentioning
confidence: 99%